Anti-Influenza Activity of C60 Fullerene Derivatives - Shoji, Masaki; Takahashi, Etsuhisa; Hatakeyama, Dai; Iwai, Yuma; Morita, Yuka; Shirayama, Riku; Echigo, Noriko; Kido, Hiroshi; Nakamura, Shigeo; Mashino, Tadahiko; Okutani, Takeshi; Kuzuhara, Takashi (PLOS ONE, 2013)
The H1N1 influenza A virus, which originated in swine, caused a global pandemic in 2009, and the highly pathogenic H5N1 avian influenza virus has also caused epidemics in Southeast Asia in recent years. Thus, the threat from influenza A remains a serious global health issue, and novel drugs that target these viruses are highly desirable. Influenza A RNA polymerase consists of the PA, PB1, and PB2 subunits, and the N-terminal domain of the PA subunit demonstrates endonuclease activity. Fullerene (C60) is a unique carbon molecule that forms a sphere. To identify potential new anti-influenza compounds, we screened 12 fullerene derivatives using an in vitro PA endonuclease inhibition assay. We identified 8 fullerene derivatives that inhibited the endonuclease activity of the PA N-terminal domain or full-length PA protein in vitro. We also performed in silico docking simulation analysis of the C60 fullerene and PA endonuclease, which suggested that fullerenes can bind to the active pocket of PA endonuclease. In a cell culture system, we found that several fullerene derivatives inhibit influenza A viral infection and the expression of influenza A nucleoprotein and nonstructural protein 1. These results indicate that fullerene derivatives are possible candidates for the development of novel anti-influenza drugs.